Burden of rheumatic diseases among people with diabetes: A systematic review and meta-analysis - Mamadapur, Mahabaleshwar; Gaidhane, Abhay M.; Padhi, Bijaya K.; Zahiruddin, Quazi S.; Sharma, Rakesh K.; Rustagi, Sarvesh; Satapathy, Prakasini; Sridhar, Sathvik B.; Shareef, Javedh; Talath, Sirajunisa; Yadav , Rajesh K.; Mehta, Rachana (Narra J, 2024)
Diabetes mellitus type 2 (DM2) is a prevalent metabolic condition affecting over 500 million people globally and associated with serious comorbidities, including various rheumatologic conditions. Some studies have reported a significant association between rheumatological conditions and DM2. However, the global burden of rheumatological conditions among people with DM2 remains unknown. The aim of this study was to assess the cumulative prevalence of rheumatological conditions in DM2 patients. An extensive electronic search was conducted utilizing multiple databases of studies published until January 2024. The quality of the studies included in the review was evaluated using a modified version of the Newcastle-Ottawa Scale (NOS). The overall quality of the studies included was rated as moderate. The review included a total of 13 studies, with 830,649 DM2 patients reported to have rheumatological conditions. Eleven studies were used to determine the individual results of rheumatoid arthritis (RA), gout, and osteoarthritis (OA). The pooled prevalence of OA was 26% (95%CI: 19–32%) and the prediction interval ranged from 6% to 51%. The pooled prevalence of gout disease was 1% (95%CI: 0.0–5.0%), and the prediction interval ranged from 0% to 99%. For RA, the combined prevalence was 0.3% (95%CI: 0.2–0.5%) and the prediction interval ranged from 0% to 5%. In conclusion, this review suggests a considerable prevalence of OA among DM2 patients, while the prevalence of RA and gout was minimal. Early diagnosis and management of certain rheumatologic conditions in individuals with DM2 may help improve health outcomes and prevent premature mortality. Further research is warranted to explore and understand the mechanisms underlying the association between DM2 and rheumatological conditions.